2011
DOI: 10.2337/dc11-1372
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and Asymptomatic Coronary Artery Disease in Type 2 Diabetic Patients With Elevated Urinary Albumin Excretion Rate

Abstract: OBJECTIVE Coronary artery disease (CAD) is the major cause of morbidity and mortality in type 2 diabetic patients. Severe vitamin D deficiency has been shown to predict cardiovascular mortality in type 2 diabetic patients. RESEARCH DESIGN AND METHODS We investigated the association among severe vitamin D deficiency, coronary calcium score (CCS), and asymptomatic CAD in type 2 diabetic patients with elevated urinary albumin excretion rate (UAER) >30 mg/24 h. This was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
2
33
2
1
Order By: Relevance
“…Two studies compared high CAC groups to low CAC groups across vitamin D levels [14,15]. One compared prevalence of CAC>100 while the other had a cut-off of CAC >400.…”
Section: Vitamin D and High Vs Low Cacmentioning
confidence: 98%
“…Two studies compared high CAC groups to low CAC groups across vitamin D levels [14,15]. One compared prevalence of CAC>100 while the other had a cut-off of CAC >400.…”
Section: Vitamin D and High Vs Low Cacmentioning
confidence: 98%
“…26 Another population-based study in patients with type 2 diabetes and elevated urinary albumin excretion rate showed that severe 25(OH)VitD deficiency (plasma level b12.5 nmol/L) is significantly associated with subclinical atherosclerosis (defined as elevated coronary calcium score ≥400). 27 In contrast, a recently published cohort study failed to demonstrate significant association between 25(OH)VitD deficiency and future development of CHD events. 28 It included 936 veterans with type 2 diabetes (96.9% men, mean age of 59.7 ± 8.4 years).…”
Section: Discussionmentioning
confidence: 88%
“…As noted, 25(OH)VitD is associated with improved endothelial function, 30 decreased vascular stiffness, 26 and decreased coronary calcification. 27 Growing body of evidence suggests that 25(OH)VitD deficiency could take part in developing hypertension and diabetes. 31 For instance, serum 25(OH)VitD may decrease the activity of renin-angiotensin-aldosterone system, which subsequently reduces blood pressure and decreases the risk of left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, vitamin D supplementation may have a role in modifying other aspects of the metabolic and cardiovascular derangements that accompany type 2 diabetes [12]. Recently, Joergensen et al [13] suggested that in high-risk type 2 diabetic patients with elevated urinary albumin excretion rate, low levels of vitamin D were associated with asymptomatic coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%